Early Life Adversity and Adult Biological Risk Profiles - Friedman, Esther M. (Psychosom Med, 2015)
OBJECTIVES: To determine whether there is a relationship between early life adversity (ELA) and biological parameters known to predict health risks and to examine the extent to which circumstances in midlife mediate this relationship. METHODS: We analyzed data on 1,180 respondents from the biomarker subsample of the second wave of the National Survey of Midlife Development in the United States (MIDUS) study. ELA assessments were based on childhood socioeconomic disadvantage (i.e. on welfare, perceived low income, less-educated parents) and other stressors (e.g., parental death, parental divorce, and parental physical abuse). The outcome variable was cumulative allostatic load (AL), a marker of biological risk. We also incorporate information on adult circumstances, including: education, social relationships, and health behaviors. RESULTS: Childhood socioeconomic adversity was associated with increased AL (B=0.094, SE=0.041) and physical abuse (B=0.263, SE=0.091), with non-significant associations for parental divorce and death. Adult education mediated the relationship between socioeconomic ELA and cumulative allostatic load to the point of non-significance, with this factor alone explaining nearly 40% of the relationship. The association between childhood physical abuse and AL remained even after adjusting for adult educational attainments, social relationships, and health behaviors. These associations were most pronounced for secondary stress systems, including inflammation, cardiovascular function, and lipid metabolism. CONCLUSIONS: The physiological consequences of early life socioeconomic adversity are attenuated by achieving high levels of schooling later on. The adverse consequences of childhood physical abuse, on the other hand, persist in multivariable adjusted analysis.